The Effectiveness of Using Social Media to Teach Writing Hortatory Exposition Text at Eleventh Grade of SMAN 1 Ngadiluwih - Nila sari; Agus Amroni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2021)
The aim of this research was to motivate students by using social media to teach writing hortatory exposition text. The researcher chooses two media such us Instagram and Facebook. The application of teaching writing of hortatory exposition text at eleventh grade of SMAN 1 Ngadiluwih by using social media Instagram and Facebook to hold the interesting and enjoyable learning activity. This research was quantitative research approach, whereas the research design used true experimental. This research chosen randomly in Instagram class (social one class) and Facebook class (social two class). The instrument used in the research was writing test. The procedure lasted 4 meeting and 1 meeting to do test. The result of t-test showed that: the mean score of Instagram class (M= 68.79) is lower than Facebook class (M= 77.07), and independent sample t-test which values of the sig-2 tailed is 0.000 and 0.000<0.005. Thus, it can be concluded that Facebook is more effective than Instagram in teaching and learning English Hortatory Exposition Text.